A new species of Pinguicula (Lentibulariaceae) from the states of Querétaro and Hidalgo, Mexico - Zamudio, Sergio; Zirahuen Ortega, Ricardo (Instituto de Ecología, A.C., 1994)
Pinguicula moctezumae, from the Río Moctezuma canyon in the Mexican states of Queretaro and Hidalgo is described as new. This species belongs to the section Orcheosanthus, subsection Violiformis, with P. gypsicola Brandegee, on account of its lanceolate-linear leaves.